Step-by-step Solution

Apply logarithm properties $\ln\left(e^{11-1y}\right)$

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Final Answer

$-11y$

Step-by-step explanation

Problem to solve:

$\ln\left(e^{11\left(-1\right)\cdot y}\right)$
1

Multiply $11$ times $-1$

$\ln\left(e^{-11y}\right)$
2

Apply the formula: $\ln\left(e^x\right)$$=x$, where $x=-11y$

$-11y$

Final Answer

$-11y$

Problem Analysis

$\ln\left(e^{11\left(-1\right)\cdot y}\right)$

Time to solve it:

~ 0.02 seconds